Một cuộc phỏng vấn xin việc điển hình (2011)
Unit 1: Introduction Unit 2: Self - Description Unit 3: Educational Experience Unit 4: Previous Job Experience Unit 5: Special Skills Unit 6: The Ideal Job Unit 7: Describe Your Greatest Strengths and Weaknesses Unit 8: Interests and Free Time Unit 9: Reasons for Leaving a Previous Job Unit 10: Handling Pressure Unit 11: Other questions Unit 12: Why do you wants this job? Unit 13: Do you have any questions? Unit 14: Gettings a job offer